If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(4k+6)=3(5k+1)
We simplify the equation to the form, which is simple to understand
2(4k+6)=3(5k+1)
Reorder the terms in parentheses
+(+8k+12)=3*(5k+1)
Remove unnecessary parentheses
+8k+12=+3+*(+5k+1+)
Reorder the terms in parentheses
+8k+12=+(+15k+3)
Remove unnecessary parentheses
+8k+12=+15k+3
We move all terms containing k to the left and all other terms to the right.
+8k-15k=+3-12
We simplify left and right side of the equation.
-7k=-9
We divide both sides of the equation by -7 to get k.
k=1.28571428571
| 87-6x=12x+23 | | 8x-5y=5 | | 6-8x=93-29x | | -90-9x=10x | | 6x*2= | | 5(1-x)-2=3x-4 | | 3x-1=14x+7 | | 117-4x=32x+17 | | 8-9x=96-37x | | -14-10x=8x+23 | | 2x-1=12-81 | | 5x-25=35 | | 2(5x-4)=4(x+7) | | (5x+6)(x-1)-(2x-5x+3)=0 | | X^3=36 | | 2n^3+7=2n^5 | | 140-7x=38x+15 | | 5n+7=27 | | (n-6)*2=4 | | (n-6)*10=70 | | 65=-4(5b+3) | | 108-3x=4x+17 | | 14-6x=6-8x | | 7(2y-3)=28 | | 8x^3+4x^2-34x+15=0 | | -3(4-2w)=10 | | 3(4-3s)=34 | | 3g+15=5g-3 | | 9x+23=3x+197 | | -3(4-2n)=19 | | -3(4-2)=19 | | 2x+3=2(2x+7) |